PENGARUH KEDISIPLINAN DAN ETOS KERJA TERHADAP KINERJA DENGAN MEDIASI KOMITMEN ORGANISASI (Studi Kasus Pada Guru SD di Wilayah Kecamatan Pati Kabupaten Pati) - Herawati Neko Rahayu, 11.52.02.0036 (Students Journal of Economic and Management, 2013)
This study aims to identify and examine  the influence of disciplinary, work ethic on the performance by mediationoragization commitment that takes an objectof primary school teachers in Pati subdistrict. Sampling was done by purposive sampling technique. From the result of purposive sampling, the sample was used in this study, totaling 156 people. Testing data technique which is used in this study include validity test by factor analysis, reliability test by Cronbach alpha formula, multiple regression analysis, and significance  tests, the coeffisien of determination to prove the hypothesis and mediation test. The result showed that the variables of organizational commitment proved to mediate the effect of discipline and work ethic on the performance of elementary school teachers in Pati subdistrict Pati regency. Discipline and work ethic has a positive and significant effect on performance. Discipline variable, work ethic and organization commitment to the performance influenced 51.7%. The remaining 48.3% is influence by other variables which is not included in the study.   Key word: discipline, work ethic, organization commitment, performance.